Warzones! - Bennett, Marguerite 1988-; Wilson, G. Willow 1982- (Marvel Worldwide, Inc., 2015)
An all-new book featuring Marvel's Mightiest Women! In a secluded corner of the Battleworld, an island nation is fiercely protected by a team of Avengers the likes of which has only ever been glimpsed before. Fighting to protect the small sliver of their world that's left, the Amazing A-FORCE stands shoulder to shoulder, ready to take on the horde!
Contains material originally published in magazine form as A-Force #1-5
Keywords: Women superheroes / Comic books, strips, etc; Good and evil / Comic books, strips, etc; Comic books, strips, etc / United States; Comic books, strips, etc; Good and evil; Women superheroes; United States; Avengers (Fictitious characters) / Comic books, strips, etc; Conspiracy / Comic books, strips, etc; Islands / Comic books, strips, etc; Traitors / Comic books, strips, etc; Monsters / Comic books, strips, etc; Graphic novels; Superhero comics; Science fiction comics; Comics (Graphic works); Comic